DEVELOPING OF ETHNOMATHEMATICS-BASED CURVED-SIDED SPACE-BUILDING MATERIALS TO IMPROVE STUDENTS' MATHEMATICAL PROBLEM SOLVING SKILLS - Annisa Fikria Hasibuan; Asrul Asrul (JME (Journal of Mathematics Education), 2024)
Incorporating cultural elements into teaching and learning activities is an effort to localize the culture around students by linking the material of the curved side space building with the architecture of the Medan Great Mosque. It is hoped that students will be involved in the learning process and develop a deeper understanding of mathematics. This development research aims to produce valid, practical, and effective ethnomathematics LKPD to improve students' mathematical problem-solving skills in class IX-3 of National Hero Junior High School. The product developed is made of Curved Side Spaces material, which includes tubes, cones, and spheres. This research uses the Research and Development method with the ADDIE model, which includes analysis, planning, development, implementation, and evaluation. The instruments used in data collection include validation sheets, response questionnaires, and problem-solving ability tests. The results showed the results of the LKPD validity test were in the very valid category with an average of 97%, while the results of the practicality of LKPD were in the very practical category of teacher questionnaires with a percentage of 95%, and so the student questionnaires with a percentage of 87%. Post-test results show an increased student's ability to solve mathematical problems, with a result of 0.72 being an effective category. So that the LKPD of Curved Side Room Building Material Based on Ethnomathematics in Medan Great Mosque Architecture to Improve Mathematical Problem-Solving Ability is valid, practical, and effective.